(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper presents the results of a study on the Effect of selected Yogasana Practices on Health Related Physical Fitness of College Students. The study is experimental study. Simple Random Pre-Test – Treatment – Post Test design is adopted. The subjects in the age group of 17 – 19 years were selected at randomly of College of Engineering Kharghar, Navi Mumbai. 30 subjects were allotted to each of the experimental and control groups.Statement of the Problem The main purpose of the study was find out the effect of training in Hatha Yogasana practices on Health Related Physical Fitness of College Students.Hypothesis It was hypothesized that there would be a significant effect of training in Hatha Yogasana practices on the selected variables namely health related physical fitness.Methodology A detailed training schedule for 12 weeks was prepared. Yogasanas were alone given as treatment. For the Health Related Physical Fitness (HRPF), the variables such as Functional Strength (FS), Trunk Strength (TS), Body Mass Percentage (BMP), Sit - Up, Flexed Arm, Bent Knee Sit - Ups, Skin Fold and Harvard Step Tests were administered in an order. The reliability and validity were suitability established as required for the instruments and scales used.Descriptive and differential statistical techniques were used. Since, „t‟ test results did not show any significant difference (Two tailed test of significance at o.o1 level is considered) between the Mean scores of pre-tests of experimental and control groups in all the nine criterion variables, the groups are equivalent with reference to these variables. Hence, ANOVA was applied. The obtained „t‟ test results reveals that there is a significant difference (one tailed test of significance at 0.05 level is considered) between the Post and Pre Post Test Scores in all the five of the Health Related Physical Fitness of college students. The other statistical techniques such as Post - test, Gain score and Effect size analyses were used to established the significance of difference already obtained through “t‟ tests.